A Dual Power Mode Q/V-Band SiGe HBT Cascode Power Amplifier With a Novel Reconfigurable Four-Way Wilkinson Power Combiner Balun - Han, Insu; Lee, Hanjung; Moon, Seong Mo; Ju, Inchan (IEEE Transactions on Circuits and Systems II: Express Briefs, 2025)
This brief presents a dual power mode (DPM) Q/V-band SiGe HBT cascode power amplifier (PA) for emerging very low-earth-orbit (VLEO) satellite communication (SATCOM). A novel reconfigurable four-way Wilkinson power combiner balun (WPCB) is proposed, where built-in a collector-to-base (CB) junction of upper HBTs in a SiGe HBT cascode is reconfigured to either reverse- or forward-biased to support high power (HP) or low power (LP) modes of the PA, respectively. This DPM scheme neither requires any lossy series switch at the PA output nor dual power supplies, which improves PA efficiency at power back off (PBO) and reduces system complexity. The DPM PA prototype is fabricated in 0.13 μm SiGe HBT BiCMOS. For HP/LP modes, the PA attains measured peak output power (POUT) and peak power added efficiency (PAE) 23.3/18.7 dBm and 30.4/25.8% at 45.0 GHz, respectively, demonstrating its DPM capability. For HP/LP modes at 45 GHz, it delivers linear POUT (PAVG) of 17.0/11.8 dBm with average PAE (PAEAVG) of 17.7/13.0% at 250MHz symbol rate DVB-S2X 64 ASPK modulation signal.
Keywords: BiCMOS; Cascode; Dual power; Earth orbits; Low earth orbit; Power; Power amplifier; Q-bands; Reconfigurable; Satellite communication; Satellite communications; V-band; Wilkinson; Balun; BiCMOS; cascode; dual power; HBT; low earth orbit (LEO); power amplifier (PA); Q-band; reconfigurable; satellite communication (SATCOM); SiGe; V-band; Wilkinson